A flexible and robust dual-network supramolecular elastic film with solvent resistance and brilliant structural colors. (1st July 2019) - Wu, Jia; Niu, Wenbin; Zhang, Shufen; Wu, Suli; Ma, Wei; Tang, Bingtao
Abstract : Structural color films were prepared by combining a Zn 2+ -crosslinked supramolecular elastic material with PS@SiO2 colloidal crystals. Abstract : In this study, a novel flexible and robust dual-network supramolecular elastic film with solvent resistance and brilliant structural colors was prepared by combining a Zn 2+ -crosslinked supramolecular elastic film with polystyrene@silica (PS@SiO2 ) colloidal crystals. This structurally colored supramolecular elastic material consisted of a covalent support network formed by three different monomers and a Zn 2+ -crosslinked polyacrylic acid (PAA) coordination network, which provided high mechanical strength and flexibility. The tensile and compression stress of this structural color reached 3.26 MPa at a strain of 187% and a pressure of 300 N. The reflectance wavelength of the structural color film remained unchanged after loading–unloading cycles and compression cycles. The structural color film could be bent and unfolded without heating or the application of an external stimulus. Moreover, the structural color film exhibited resistance to solvents in saturated organic vapors and remained color invariant.